Emerging Roles of Perivascular Adipose Tissue in Regulation of Vascular Functions - Yang, Z.; Montani, J. P. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
Clinical and experimental studies provide increasing evidence that obesity is a major cardiovascular risk factor and that the adipose tissue is not just for regulation of lipid and energy homeostasis. Accordingly, the endocrine secretion of adipose tissue is implicated in the pathogenesis of vascular diseases. Whilst the functions of visceral and subcutaneous adipose tissue are relatively well studied, the role of perivascular adipose tissue in regulation of vascular functions is usually ignored. Emerging evidence indicates that perivascular adipose tissue is involved in the regulation of various physiological and pathological processes such as vascular smooth muscle contraction, vascular wall remodeling and inflammation, and, consequently, atherosclerosis and hypertension. Here we present an updated overview of vascular adipobiology, focusing on perivascular adipose tissue.
Keywords: atherosclerosis